Health problems among women in sports: The Female Athlete Triad - Patrycja Karkos; Katarzyna Kuśmierczyk; Marta Jurga; Kacper Jurga; Bartłomiej Grodziński; Elena Sztemberg; Hanna Gruszczyńska; Michalina Grzelka; Julia Głoskowska; Katarzyna Kuleta (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Over the years the participation of women in sports and physical activities has significantly increased. The rise in the number of female athletes has brought to attention the health issues specific to this population. The Female Athlete Triad is a syndrome in which the affected woman presents the combination of three intertwined conditions such as (1) low energy availability, (2) menstrual dysfunction, and (3) low bone mineral density. The crucial factor in the pathophysiology is energy imbalance, which leads to impairment of the reproductive and skeletal system, eventually having a very harmful effect on the whole organism and leading to appalling short-term and long-term consequences. It affects women of all ages and from every sports discipline, but most at risk are those in adolescence involved in sports that prioritize leanness and endurance. Purpose: The objective of this article is to review the current state of knowledge about the Female Athlete Triad, spreading awareness of this syndrome, which is still very low in society, and highlighting the importance of early identification and multidisciplinary treatment to prevent serious complications. Materials and methods: The review was based on a comprehensive analysis of the available literature sourced from PubMed, Google Scholar, and other scientific articles, which was searched by using listed keywords and analysed for topic relevance and knowledge currency.